Epigenetic Regulation of Cardiac Neural Crest Cells - Yan, Shun; Lu, Jin; Jiao, Kai (Frontiers in Cell and Developmental Biology, 2021)
The cardiac neural crest cells (cNCCs) is a transient, migratory cell population that contribute to the formation of major arteries and the septa and valves of the heart. Abnormal development of cNCCs leads to a spectrum of congenital heart defects that mainly affect the outflow region of the hearts. Signaling molecules and transcription factors are the best studied regulatory events controlling cNCC development. In recent years, however, accumulated evidence supports that epigenetic regulation also plays an important role in cNCC development. Here, we summarize the functions of epigenetic regulators during cNCC development as well as cNCC related cardiovascular defects. These factors include ATP-dependent chromatin remodeling factors, histone modifiers and DNA methylation modulators. In many cases, mutations in the genes encoding these factors are known to cause inborn heart diseases. A better understanding of epigenetic regulators, their activities and their roles during heart development will ultimately contribute to the development of new clinical applications for patients with congenital heart disease.